The Islamic Foundations of Halal Food Gastronomy in ‎Malaysia ‎ - Siti Jamilah Mohd Sukri; Nurul Widad Fitri Muhammad; Anis Hamizah Hamid; Nurrulhidayah Ahmad Fadzlillah (Rabbanica: Journal of Revealed Knowledge)
The current scenario is witnessing halal food culture being widely practised by Muslims and non-Muslim because of their confidence in its quality in terms of safety, hygiene, and nutrient composition. The availability of halal food becomes a positive factor in attracting tourists, whether at the domestic or international level, when selecting a travel destination. Recognise that, in this scenario, some authorities are interested in developing gastronomy tourism to provide a joyful experience for tourists. The purpose of this paper is to provide an overview of halal food culture and its relationship to the gastronomy field. Secondly, the researcher also attempts to identify the sources of halal food gastronomy from a Shari’ah perspective. To write this paper, library research has been conducted by reviewing secondary sources. The researcher has applied the thematic content analysis technique to analyse the selected library sources. The result signifies six primary sources of halal gastronomy, which are: Al-Quran, Al-Sunnah, Al-Ijma’, Fatwa, Al-Uruf, Al-Maslahah and Al-Dharuriyyat.